Implementation of the Scaffolding Method in Improving Islamic Religious Education Learning Outcomes on the Material of Improving the Ability to Read and Write the Qur'an through Innovative Class Methods with Visual Media at SMP Negeri 2 Perbaungan - Apriani, Nurhapni; Harahap, Diana Fajar Anggraini; Ritonga, Muhammad Ali Sukri; Saidah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using the scaffolding method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study indicate that the scaffolding method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.81%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Thus, the use of the scaffolding method can be used as an alternative to improve student learning outcomes in Islamic religious education learning